Mudah Belajar Bahasa Inggris Menggunakan Media Sosial Youtube - Lilis Sukmawati; Heribertus Aji Putra Purwanto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2020)
This research was conducted in an effort to increase interest in learning English through Youtube media. while going to English education in our daily lives. especially the students who are studying. e.g. English is one of the common subjects but its existence is very important in supporting various other subjects. therefore, this study uses qualitative method with six (6) sample images and questionnaires as well as method method and transferability. the results of the learning force using Youtube content media increased can be in line with the communication strategy that dis dias over the target of learning.